Cyberspace: is it useful or not in the world of education? - Salam, Muhammad Yusuf; Mudinillah, Adam; Amrina, Amrina; Suharmon, Suharmon; Shidqi, Muhammad Husni; Oktavia, Nur Afni (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aims to enhance the usage of Instagram among educators and students. Currently, in the field of education, this application is primarily used as a joining material or a place to take pictures. The use of social media in the form of Instagram can aid in children’s learning by increasing their activity and creativity. Additionally, the virtual world of Instagram makes it easy for learning material to be repeated anywhere and anytime. In this study, data was collected from Instagram users using a survey method that included interviews. The results showed that users complain of high data usage and difficulties in using the application as a learning platform. Therefore, it can be concluded that Instagram is primarily used by the general audience as a joining material and mood booster. This led the researchers to take the initiative to conduct further research on the potential use of Instagram in education.